Stylosanthes for pasture development. An overview of ILCA's experience in Nigeria - Mohamed-Saleem, M.A. (International Livestock Centre for Africa, 1994)
To improve livestock productivity in sub-Saharan Africa sustainable solutions to seasonal deficiencies in feed availability and quality are required. Traditionally, livestock rearing has been the specialised vocation of nomadic and transhumant pastoralists and therefore, for a long time, technological changes in livestock and feed production management strategies have been targeted at this group. During the last two decades nomadic pastoralists have been settling in large numbers for several reasons and for a long time settled pastoralists were not considered a potential target group for improving livestock productivity in sub-Saharan Africa. When ILCA started work in the subhumid zone of Nigeria in 1987, it saw an opportunity to complement national research by introducing improvement interventions among sedentarised agropastoralists. Settled pastoralists take up cropping on a regular basis and part of their available resources are diverted from livestock to cropping activities. During the last two decades the number of arable farmers investing in livestock has also increased. These trends signal an emergence of more strongly integrated crop-livestock systems across sub-Saharan Africa which may eventually help cope with the need for greater agricultural output. To overcome feed deficiencies, various forages, including Stylosanthes, were found promising. However, until recently none of the species were adopted by the farmers because there is no tradition of growing forages in West Africa. Hence, there had to be closer interaction with the producers to biotechnically and socioculturally tailor forages to the prevailing farming systems. This required a multidisciplinary team to address the complex issues of species compatibility, competition, rotational sequences and management for developing forage-crop associations.These were the main focus of ILCA feed development research and the genus Stylosanthes provided the principal germplasm for on-station and on-farm research. Major findings by ILCA from this work during the past decade are summarised in the papers presented at this workshop.